If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 + 6a + -18 = 18 Reorder the terms: 14 + -18 + 6a = 18 Combine like terms: 14 + -18 = -4 -4 + 6a = 18 Solving -4 + 6a = 18 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 6a = 18 + 4 Combine like terms: -4 + 4 = 0 0 + 6a = 18 + 4 6a = 18 + 4 Combine like terms: 18 + 4 = 22 6a = 22 Divide each side by '6'. a = 3.666666667 Simplifying a = 3.666666667
| 3/4-0.2 | | 7x(3x+5)-11x-6=-16 | | 21(7x)=28(5x+2) | | 0.5x+2.5=10 | | 4s+12t=4 | | 6=18y | | -5s+t=11 | | 13x+10=5x-30 | | 9.54=-2x+2(x+4.77) | | lnx=35.7 | | v^2+4v-10=0 | | 40+19.95x=59.85+29.95x | | 14x(2-3)=xy | | -1/5-1/2v=-1/7 | | 7x^5/x^5 | | 3a+2b+c=n | | 2/3x-5=3 | | x^2+2xy+y^2-9=25 | | 5x^3-13x+20=0 | | (x-3).3+(2x-5).4+4x=0 | | 11x+19y=13 | | (y-24)+(3y-20)= | | 7!/(4)!3! | | 32.475+(4.87*30)= | | 12x/10y*4y/3xy | | 13x+14x+x=57 | | -10(2x+4)=-(-8-9x)+3x | | w-3.53=9.9 | | 4.2=t-5.4 | | -11(3)2(.12(-12))= | | v+5.84=8.29 | | (1/3)(27)= |